Original articlePrognostic significance of the markers IDH1 and YKL40 related to the subventricular zone - Batista, Kelvin Manuel Pińa; Vega, Ivan Fernandez; Eulate-Beramendi, Sayoa Alvarez de; Morales, Julio Cesar Gutierrez; Kurbanov, Almaz; Asnel, Dorisme; Meilan, Angela; Astudillo, Aurora (Folia Neuropathologica, 2015)
Glioblastoma multiforme (GBM), a highly aggressive brain cancer characterized by uncontrolled proliferation, resistance to cell death, angiogenesis, and vascular edema, remains one of the deadliest types of cancer. The subventricular zone (SVZ) harbors cells with great proliferative potential, and the microenvironment within the SVZ is permissive to growth and proliferation. This neurogenic niche is suspected to be a vulnerable site for the origin of subtypes of GBM. The aim of our study was to determine the immunohistochemical expression of mIDH1 and YKL40 in relationship to the SVZ of GBMs. YKL40, also known as chitinase-like protein 1, is included as a mesenchymal marker and associated with a poor prognosis. The protein is a secreted inflammatory molecule with no chitinolytic activity. However, the mutation of IDH1 (mIDH1) has been found in the cytoplasm and peroxisomes of 70-80% of secondary GBMs. In our study we found that YKL40-positive GBM is significantly linked to SVZ types IV and V (p < 0.0001). Our results show the diversity among GBMs related to the SVZ, which should be considered in the design of future targeted therapies. There was a significant impact of patient age, mIDH1 positivity, SVZ type III, and chemoradiotherapy on overall survival.